Cloning of human tumor necrosis factor (TNF) receptor cDNA and expression of recombinant soluble TNF-binding protein. - Gray, P; Barrett, K; Chantry, D; Turner, M; Feldmann, M (1990)
The cDNA for one of the receptors for human tumor necrosis factor (TNF) has been isolated. This cDNA encodes a protein of 455 amino acids that is divided into an extracellular domain of 171 residues and a cytoplasmic domain of 221 residues. The extracellular domain has been engineered for expression in mammalian cells, and this recombinant derivative binds TNF alpha with high affinity and inhibits its cytotoxic activity in vitro. The TNF receptor exhibits similarity with a family of cell surface proteins that includes the nerve growth factor receptor, the human B-cell surface antigen CD40, and the rat T-cell surface antigen OX40. The TNF receptor contains four cysteine-rich subdomains in the extracellular portion. Mammalian cells transfected with the entire TNF receptor cDNA bind radiolabeled TNF alpha with an affinity of 2.5 x 10(-9) M. This binding can be competitively inhibited with unlabeled TNF alpha or lymphotoxin (TNF beta).